Pengaruh Kepemilikan Fasilitas Telekomunikasi dan Akses Internet terhadap Capaian Proses Pendidikan di Indonesia - Rahmadani, Alif Hidayah Nur; Hutabarat, Josephin Pirdinansius; Prakoso, Nurihisha Nadya Putri; Kartiasih, Fitri (Politeknik Statistika STIS, 2024)
Fulfilling access to education is one of the Sustainable Development Goals targets to ensure quality education. In the digital era, telecommunication facility ownership and internet access are key to enhancing educational outcomes. This study aims to analyze telecommunication facility ownership contribution and internet access to educational outcomes in Indonesia. The research method used descriptive analysis and inferential analysis with multiple linear regression to analyze the effect of telecommunication facility ownership and internet access on educational outcomes. The results showed that the percentage of computer use and the percentage of cellular phone use had a significant effect on increasing the mean years of schooling. Meanwhile, the variable Percentage of Internet Use has a significant effect on reducing Mean Years of Schooling. The Internet is often used to access social media, online games and YouTube and increase the phenomenon of homeshcooling. The government should provide socialization and education on internet usage and improve telecommunication facilities in schools to improve student learning methods.